Comparative Genomic Study of Lactobacillus jensenii and the Newly Defined Lactobacillus mulieris Species Identifies Species-Specific Functionality - Catherine Putonti (American Society for Microbiology, 2020)
ABSTRACT Lactobacilli are dominant members of the “healthy” female urogenital microbiota. One of these species, Lactobacillus jensenii, is routinely identified in the urinary microbiota of women both with and without urinary tract symptoms. In March 2020, the new bacterial species Lactobacillus mulieris was introduced, and phylogenetic and average nucleotide identity analysis identified eight L. jensenii strains that should be classified as members of the L. mulieris species. This prompted our phylogenomic study of all publicly available L. jensenii and L. mulieris genome sequences. While there is little variation in the 16S rRNA gene sequences, the core genome shows a clear distinction between genomes of the two species. We find eight additional strains of the species L. mulieris among these genomes. Furthermore, one strain, currently classified as L. mulieris UMB7784, is distinct from both L. jensenii and L. mulieris strains. As part of our comparative genomic study, we also investigated the genetic content that distinguishes these two species. Unique to the L. jensenii genomes are several genes related to catabolism of disaccharides. In contrast, L. mulieris genomes encode several cell surface and secreted proteins that are not found within the L. jensenii genomes. These L. jensenii-specific and L. mulieris-specific loci provide insight into phenotypic differences of these two species. IMPORTANCE Lactobacillus species play a key role in the health of the urinary tract. For instance, Lactobacillus crispatus and L. jensenii have been found to inhibit uropathogenic Escherichia coli growth. While L. crispatus is typically found only within the microbiota of women without lower urinary tract symptoms (LUTS), L. jensenii has been found in the microbiota of women both with and without LUTS. With the recent introduction of the new species Lactobacillus mulieris, several strains of L. jensenii were reclassified as L. mulieris based upon gene marker and average nucleotide identity. We took a phylogenomic and comparative genomic approach to ascertain the genetic determinants of these two species. Looking at a larger data set, we identified additional L. mulieris strains, including one distinct from other members of the species—L. mulieris UMB7784. Furthermore, we identified unique loci in each species that may have clinical implications.